Behavior of highly ductile fiber–reinforced concrete columns under eccentric loading. (October 2021) - Li, Ruizhe; Deng, Mingke; Zhang, Yangxi
Abstract: Highly ductile fiber–reinforced concrete (HDC) is characterized by a tensile strain–hardening behavior and high compressive toughness, which is expected to alleviate the cracking and durability problems induced by the brittleness of high–strength concrete (HSC). In this study, HSC was substituted with HDC to construct columns. Six reinforced HDC (R/HDC) columns and two reinforced HSC (R/HSC) columns were constructed and tested under compressive loads with different eccentricities. The crack patterns, failure modes, lateral deflection curves, load–displacement curves, and strains of concrete and rebars were investigated. The test results revealed that the R/HDC column has a better failure mode and cracking pattern compared to the HSC column. A good synergy work performance between HDC and rebars significantly improved the utilization of the longitudinal rebars. A calculation method for the bearing capacity of the R/HDC column was proposed. The calculated results were in good agreement with the experimental results. The load–moment interaction curves ( N – M curves) of the R/HDC column were calculated and plotted. Subsequently, the effects of HDC compressive strength, HDC tensile strength, the reinforcement strength, and longitudinal reinforcement ratio on the bearing capacity of the R/HDC column were studied using parametric analysis. The results indicate that a high tensile strain can guarantee the efficient utilization of the tensile strength of HDC.